IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN DAERAH DALAM PENYUSUNAN ANGGARAN PADA BKPSDM KABUPATEN JAYAPURA - Daeng Nyengka, Idham Chalid; Marissa, Elsyan R.; Aedah, Nur (Universitas Cenderawasih, 2024)
The Local Government Information System (SIPD) integrates development, financial, and local government information to support budgeting. This study aims to analyze the implementation of budgeting through SIPD in BKPSDM Jayapura Regency, using the theory of George C. Edward III theory which includes four indicators: communication, resources, disposition, and bureaucratic structure. This research is important because optimizing the use of SIPD can improve transparency, accountability, and efficiency of local budget management. Communication is realized through socialization by Bapeda to ensure employee understanding of budget preparation. Resources include the readiness of labor, funds, and adequate facilities. Disposition is shown by technical competence and employee understanding of implementation rules. Supportive bureaucratic structures, such as clear procedures and effective coordination, also determine the success of implementation. The results showed that the implementation ran optimally with the support of socialization, employee readiness, and the role of the government, despite facing obstacles such as delays in data input, budget limitations, and constraints on information validity. This implementation is in accordance with Permendagri No. 70/2019 on SIPD.